(untitled) (Docentes 2.0 Journal, 2024)
English has become an indispensable tool in various areas, such as business, tourism, and education. The central objective of analyzing the incidence of a didactic sequence based on Rebecca Oxford’s taxonomy on the communication skills of tenth-grade students of the I.E. Técnico Industrial Laureano Gómez Castro, in the municipality of Aguachica, department of César in Colombia. The proposed methodology was based on an interpretive paradigm, with a qualitative approach of phenomenological design and a method oriented from action research. The data collection techniques and instruments were the diagnostic and final knowledge test, participant observation, field diary, and semi-structured interviews. The results highlight that the design of the didactic sequence mainly benefits those students with a greater interest in foreign languages ??and a higher level of proficiency than their peers. Implementing constant, well-organized, and designed activities based on authentic material was revealed as an effective means to increase the practice of expression and production in English. In short, creating didactic sequences that promote learning strategies and interaction in the target language, using competition and dynamics, motivates students to participate actively. This approach significantly improves both the learning process and the student confidence.